Efficacy and Clinical Determinants of Antipsychotic Polypharmacy in Psychotic Patients Experiencing an Acute Relapse and Admitted to Hospital Stay: Results from a Cross-Sectional and a Subsequent Longitudinal Pilot Study. (27th January 2014) - Iasevoli, Felice; Buonaguro, Elisabetta F.; Marconi, Massimo; Di Giovambattista, Emanuela; Rapagnani, Maria Paola; De Berardis, Domenico; Martinotti, Giovanni; Mazza, Monica; Balletta, Raffaele; Serroni, Nicola; Di Giannantonio, Massimo; de Bartolomeis, Andrea; et al.
Abstract : Background. Antipsychotic polypharmacy is used in several psychiatric disorders, despite poor evidence existing to support this practice. Aim. We evaluated whether psychotic patients in acute relapse exposed to antipsychotic polypharmacy (AP + AP) showed different demographic, clinical, or psychopathological features compared to those exposed to one antipsychotic (AP) and whether AP + AP patients showed significantly higher improvement compared to AP patients after a 4-week treatment. Methods. Inpatients were subdivided into AP + AP and AP ones. In the cross-sectional step, patients were compared according to demographics, clinical variables, and scores on rating scales. In the longitudinal step, patients remained for 4 weeks under admission medications and were compared for clinical improvement. Results. AP + AP patients were more frequently diagnosed with schizophrenia and mental retardation as a comorbid illness. AP + AP patients were more frequently under first-generation antipsychotics and had worse clinical presentation. After 4 weeks of treatment, both AP + AP and AP patients improved compared to the baseline. However, AP patients scored significantly less than AP + AP patients at the Clinical Global Impression Scale at the 4-week time point but not at the baseline, indicating a treatment-specific improvement. Conclusions. Antipsychotic polypharmacy may be offered to specific types of psychotic patients. However, efficacy of this strategy is limited at best.